Features and Regional Disparities of Consultancy Services in Romania - Tudor Ciumara; Iulia Lupu (Amfiteatru Economic Journal, 2016)
The impact of the knowledge based society, especially on knowledge intensive business services, proved to have a really significant influence on the development of services industry. Consultancy services are acknowledged as innovation-intensive and knowledge-intensive business services at the same time. On the base of qualitative and quantitative research, by combining the disparities analysis with logical ranking, critical assessments and explanatory associations, comparative analysis, and empirical research, this article aims to contribute to a better appreciation and understanding of the consultancy services sector in Romania, as part of the larger family of knowledge intensive business services. The regional differences of business and personalized consultancy services are considered for discussion and revealed in the specific of the national network that has a clearly defined center. The concentration of the consultancy companies and most employees in four regions reflects the theory according to which the supply of these services is unevenly distributed, following the potential clients from better developed areas of the country. In all four types of analyzed consultancy activities, the total profit is bigger than economic loss. The disparities between regions are also supported by the dynamic evolution of the consultancy sector in Romania.
Keywords: L84; R31; 330; knowledge intensive business services (KIBS); business and personalized consultancy services; regional differences.